Effect of Pest Management Strategies on Crop Damage and Yield in Maize in Tanzania - Bomami, Daniel (American Journal of Agriculture, 2024)
Purpose: The aim of the study was to assess effect of pest management strategies on crop damage and yield in maize in Tanzania. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that integrated pest management (IPM) techniques significantly reduce crop damage and enhance yield. Traditional chemical control methods, while effective in the short term, often lead to pest resistance and can negatively impact the environment and non-target species. In contrast, IPM approaches, which combine biological control agents, crop rotation, resistant maize varieties, and minimal use of pesticides, offer sustainable long-term benefits. Study have shown that fields employing IPM strategies experience lower levels of pest infestation and crop damage compared to those relying solely on chemical pesticides. Additionally, these methods contribute to higher maize yields and improved economic returns for farmers, as they reduce input costs and promote ecological balance. The study underscores the importance of adopting diverse and integrated pest management practices to achieve optimal maize production and sustainability. Implications to Theory, Practice and Policy: Ecological theory, resource-based theory and systems theory may be used to anchor future studies on assessing the effect of pest management strategies on crop damage and yield in maize in Tanzania. Develop and promote the adoption of innovative pest monitoring technologies, predictive models, and decision support tools that enable real-time pest management decisions based on dynamic environmental and pest population data. Implement policy incentives, subsidies, and certification programs that promote the adoption of IPM practices among farmers.